Parental education and family status – association with children's cigarette smoking - Žaloudíková, Iva; Hrubá, Drahoslava; Samara, Ibrahim (Central European Journal of Public Health, 2012)
Background: Social influences are among the most important factors associated with children's and adolescents' smoking. Social norms in families, peer groups, professional and municipal communities influence the individuals ones by the process of socialization obtained mainly by interactions and observations. Especially social context of the home environment expressed by household smoking restriction serves as a socialization mechanism that dissuades from the using of tobacco. Parental anti-smoking socialization practices (their attitudes and knowledge about children smoking, discussion about smoking in appropriate quality and frequency, smoking environment in homes) are influenced by their education and family status. Methods: Markers of social environment (the level of mothers' and fathers' education, family status) were investigated during interview with 5th graders included in the cohort participating in the programme "Non-smoking Is Normal". Data about the self-reported exposure to passive smoking at homes and cars were taken into consideration. Information about discussions with parents about smoking, opinions about adults smoking, experimentation with smoking, and concurrent decision about smoking in the future were obtained from 766 children aged 11 years. Those who did not know parental education or family status were excluded from the evaluation. Differences were evaluated using the chi-square, Mantel-Haenszel, Fisher and Yates corrected tests in the statistic software Epi Info, version 6. Results: The level of mothers' and fathers' education significantly influenced the exposure of children to passive smoking. Compared to families of higher educated parents, children living in families with middle and low levels of parents' education were significantly more exposed to environmental tobacco smoke at home and in car (RR 1.38; 95% CI 1.04–1.83) and fewer of them live in non-smoking environments. In the whole cohort, 67.5% children have not smoked even one puff yet, 17.2% reported one single attempt, and 15.4% smoked repeatedly. The level of parents' education had no influence on children's concurrent smoking experimentation or on their concurrent decision about smoking in the future. There was also no difference in number of children who obtained cigarettes from their parents and parents' level of education (about 6%). When the level of maternal education was combined with the family status, significant differences were found. Compared to children living with two biological parents (highly educated mother), children from other groups more often reported current experimentating with smoking and lower number of those decided not to smoke in the future. No significant differences were found in other markers of knowledge and attitudes between children from analysed social family groups. Conclusion: In our study, the parental education has significantly influenced exposure of children to passive smoking at homes and in cars, but had no effect on children's opinions and attitudes about smoking. Higher education of mothers and family status significantly lowered the frequency of current experimentation and decision about future smoking among children living in families with two biological parents of whom mother attained higher education. It is necessary to seek ways for improving parental concern about smoking prevention.
Keywords: Educational Status; Tobacco Smoke Pollution; znečištění tabákovým kouřem; Smoking; Female; stupeň vzdělání; rodina; dítě; ženské pohlaví; kouření; lidé; Male; Social Environment; sociální prostředí; Health Knowledge, Attitudes, Practice; zdraví - znalosti, postoje, praxe; Family; Child; mužské pohlaví; Humans